Variability of mode of experiencing oneself in relation to subjectively important interactions - Gasiul, Henryk; Konopka, Agnieszka (Studia Psychologica: Theoria et praxis, 2003)
The focus of this article is on self-feeling and how it changes as a result of important relationships. Self-feeling is, recording to Gasiul a basic dimension of experience of oneself and indicates on a character of emotional self. The research work carried out on a group of 60 persons of 22-28 years of age (30 men and 30 woman). Self-feelings and feelings towards non-personal and personal objects which stay in relation to oneself were analysed. There are differences between a mode of experiencing of oneself in relations with persons and relations with non personal objects. The self-feelings are stronger than feelings to non- personal objects. But in relations with persons stronger feelings to object then to self were observed.